2002
DOI: 10.1046/j.1365-2141.2002.03763.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring polycythaemia vera with fluorescence in situ hybridization: additional cryptic 9p is the most frequent abnormality detected*

Abstract: Summary. Between 1986 and 2001, 220 patients with polycythaemia vera (PV) were studied using conventional cytogenetics. Of 204 evaluable patients, 52 (25AE4%) had clonal abnormalities. The recurrent chromosomal rearrangements were those of chromosome 9 (21AE1%), del(20q) (19AE2%), trisomy 8 (19AE2%), rearrangements of 13q (13AE4%), abnormalities of 1q (11AE5%), and of chromosomes 5 and 7 (9AE6%). Subsequent analysis of 32 patients, performed at follow-up of up to 14AE8 years, revealed new clonal abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 37 publications
2
47
0
6
Order By: Relevance
“…37,38 As loss of the Y chromosome can be found in a significant proportion of older males in the absence of any clonal haematological disorder, the pathological significance of this finding is uncertain. 38 Trisomy 8 was the next most common clonal abnormality and has also been reported in a wide range of other myeloid disorders [39][40][41][42] and in CML patients treated with interferon. 26,40,43,44 It has been postulated that the emergence of trisomy 8 during regression of the CML clone may represent the re-emergence of polyclonal haematopoiesis in a patient with underlying constitutional mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 As loss of the Y chromosome can be found in a significant proportion of older males in the absence of any clonal haematological disorder, the pathological significance of this finding is uncertain. 38 Trisomy 8 was the next most common clonal abnormality and has also been reported in a wide range of other myeloid disorders [39][40][41][42] and in CML patients treated with interferon. 26,40,43,44 It has been postulated that the emergence of trisomy 8 during regression of the CML clone may represent the re-emergence of polyclonal haematopoiesis in a patient with underlying constitutional mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…Polycythemia vera (PV), idiopathic myelofibrosis (IMF) and essential thrombocytosis (ET) are clonal myeloproliferative disorders whose shared features include origin in a multipotent hematopoietic progenitor cell (1), cytogenetic abnormalities of chromosomes 1,8,9,13 and 20 (2), growth factor-independent in vitro hematopoietic colony formation(3) and epigenetic abnormalities, such as increased granulocyte PRV-1 mRNA expression(4) and impaired megakaryocyte and platelet thrombopoietin receptor protein (Mpl) expression (5). Taken together, these shared phenotypic and genotypic features suggest that PV, IMF and ET are pathogenetically related.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these and other studies suggested that gene(s) on 9p, rather than 9q, are crucial to the pathogenesis of PV. 93 In an attempt to clarify further the genomic regions that cause the PV phenotype, Kralovics et al 94 carried out a genome-wide microsatellite screen for LOH. Three genomic regions were identified on chromosomes 9p, 10q and 11q, with LOH of the 9p being found in a third of cases, making it the most frequent chromosomal lesion described at the time.…”
Section: Chromosomementioning
confidence: 99%